STRATEGI PENGEMBANGAN KOMUNITAS PETERNAK SAPI DI WILAYAH PERBATASAN NEGARA (STUDI KASUS: KABUPATEN BELU, NUSA TENGGARA TIMUR) - Hamonangan, Adventus Daniel; Laksmono, Bambang Shergi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study discusses the Community Development Strategy for Cattle Breeders in Border Areas, Belu Regency. This research on the development strategy of the cattle rancher community will be analyzed in terms of planning and policy, political and social action, and awareness and education. This study uses a qualitative method with purposive sampling. The results of this study are the first strategy in community development used in planning in making programs/policies that are bottom-up by considering the skills of the local community. Cattle raising is one of the skills in the Belu Regency. These skills then included in the government's priority program through Presidential Instruction No. 1 of 2021. The Mootaain border area in Belu Regency is given a program to provide cattle seeds and prepare a market for selling their livestock. The second strategy is to carry out political and social actions, such as participation in farmer groups and social support among farmer groups. The third strategy is awareness and education. This strategy is implemented by providing training for cattle farmers. The training provided is various, such as inseminator training, namely artificial insemination of cattle, processing of feed for ruminants, and procedures for cultivating forage for livestock. Recommendations from this research are that it is necessary to strengthen farmer group communities, support CSR in program development, and add professionals from the central government in Belu Regency.